'Doggy's Got Teeth … Lots of Teeth': Representations of children and the canine in horror film and fiction. Issue 1 (30th April 2012) - Steel, Jayne
This article examines the various ways in which representations of children and their relationships with the canine (the dog or the wolf) are portrayed in contemporary horror film and fiction. The discussion suggests how these contemporary representations are influenced by former narratives located in myth and fairy tale. Important issues concerning gender are debated, with the first part of the article interrogating representations of female children and the second part of the article interrogating representations of male children. The discussion includes close readings of several key texts, including Little Red Riding Hood, The Lost Boys, The Omen and Cujo. These readings suggest how such narratives are often symptomatic of deep-seated, and often gendered, cultural anxieties that manifest clear moral warnings. Alternatively, representations of children and the canine can be more ambiguous. While some representations seem to translate into a liberal humanist hope, or desire for, the existence of an altruistic or divine entity, a goodness that is inherent to the taming of an aberrant supernatural force, other representations might be symptomatic of the horror that is threatened by the potential unleashing of an untamable human or inhuman, natural or supernatural, madness or disease that is endemic to modern culture and society.